Factors Affecting Recidivism of Persons Deprived of Liberty at Tabaco City District Jail - Desman Onsat; Domingo Breva Jr (Philippine Association of Institutions for Research, Inc., 2023)
Recidivism is a term used to describe the tendency of a person who has been released from prison or other Detention facilities to re-offend and return to incarceration. The study aimed to identify the factors that affect the recidivism of persons deprived of liberty at Tabaco City District Jail using a descriptive-quantitative research design. The data were collected through a survey questionnaire administered to 100 selected PDL who were detained or had been released and returned to the jail. The study found several factors contributing to recidivism, including lack of employment opportunities, substance abuse problems, lack of education and skills, and poor social support. The findings suggest the need for more comprehensive rehabilitation and reintegration programs that address these underlying factors to reduce the likelihood of repeated offenses and promote successful re-entry into society. These programs should focus on providing educational and vocational training, substance abuse treatment, and social support to help PDL successfully reintegrate into their communities. This is useful for policymakers and practitioners in the criminal justice system to develop and implement more effective interventions to reduce recidivism rates among persons deprived of liberty at Tabaco City District Jail.